Students’ Concept Construction Errors In Online Learning - Sihite, Jettson; Wyrasti, Andi Fajeriani; Irnandi, Irfan (Universitas Muhammadiyah Mataram, 2022)
A well-constructed concept can aid pupils in comprehending any learning content. However, as seen by how students solve math problems, the construction process frequently encounters flaws. Students make various conceptual construction errors in online learning. This is a qualitative study conducted on Mathematics Education students of Universitas Papua. The purpose of this study was to determine the errors made by students in constructing concepts of functions during online learning. Five subjects were selected as the subjects. They were chosen by using the purposive sampling technique. The instrument was developed using material from online lectures on functions and has been validated by experts in the field of mathematics education. The findings indicated that there were five misconstruction concepts, i.e. pseudo construction, construction holes, mis-logical construction, mis-analogical construction, and misconstruction in problem-solving. For further research, to avoid unnecessary construction errors, it is recommended that before the learning process is carried out, the teacher should know the construction of students’ concepts, so that the process of students’ conceptual change in online learning can be known.